Preparation method of high-purity crystalline cristobalite sand
Through artificial synthesis method, high-purity water glass is prepared by mixing heating of silicon source, high soda ash and deionized water, and amorphous high-purity silica powder is prepared in combination with steps such as standing aging, filtration and drying. Then, it is converted into crystalline cubic quartz through crystallization transformation and chlorination removal processes, solving the problem of high cost and amorphous products of synthesis of high-purity crystalline quartz sand in the prior art, achieving high purity and excellent mechanical, heat resistance and optical properties.
Patent Information
- Application Number
- CN202510170575.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-17
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-02-17
AI Technical Summary
The method of synthesizing high-purity crystalline quartz sand in the prior art has problems such as high cost, long production cycle, low safety and difficulty in popularizing on a large scale. Most of the products are amorphous, resulting in defects such as bubbles and flocs in quartz glass products, reducing their mechanical, heat resistance and optical properties.
Using artificial synthesis, a high-purity water glass is prepared by mixing and heating the silicon source, high-sodium ash and deionized water, and then mixed with high-purity acid to form a precipitate, and amorphous high-purity silica gel powder is prepared by standing aging, filtration and drying. Then, using crystallization transformation and chlorination removal processes, the amorphous silicone powder is converted into crystalline cubic quartz and impurities are removed, and high-purity crystalline cubic quartz sand is finally obtained.
It has achieved high-purity crystalline cubic quartz sand preparation with low cost, high yield and low safety risks. The product purity reaches 5N~7N levels, with lower bubble and floc content and better mechanical, heat resistance and optical properties.
Smart Images

Figure CN119911913A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of quartz material preparation, and in particular to a method for preparing low-cost high-purity crystalline cristobalite quartz sand. Background Art
[0002] High-purity quartz is an important basic inorganic material. Due to its excellent physical and chemical properties such as excellent chemical stability, extremely low volume expansion coefficient, extremely high heat resistance, high insulation and voltage resistance, high mechanical properties, and high light transmittance, it is widely used in photovoltaics, semiconductors, communications, optics, aerospace, military industry and other industries.
[0003] With the development of various high-tech industries, higher requirements are put forward for high-purity quartz sand. At present, the preparation technology of high-purity quartz mainly includes natural quartz purification and artificial synthesis. Since the purity of naturally purified quartz sand is limited by natural quartz minerals and purification technology, it can no longer meet the needs of various high-tech industries. Therefore, artificial synthesis of quartz sand is the only way to obtain ultra-high purity quartz sand.
[0004] At present, the main methods for artificially synthesizing quartz sand include gas phase synthesis, chemical precipitation and sol-gel methods, among which: the gas phase synthesis method (for example, Chinese patent application CN116375315A discloses a method for preparing titanium-doped synthetic quartz sand) requires high temperature conditions and complex chemical equipment, and its product contains a large amount of HCl (hydrogen chloride) vapor, so it has high requirements for reaction equipment and waste gas treatment; the chemical precipitation method (for example, Chinese patent application CN115676842A discloses a method for preparing high-purity quartz sand using ultrafine silicon powder) has low cost but needs to reduce the impurity content in the product by means of ion exchange, etc., the amount of ion exchange resin used is large and the resin cleaning, regeneration and other processes require a large amount of acid and water resources; the sol-gel method (for example, Chinese patent application CN114105150A discloses a method for synthesizing silicon dioxide powder using organic silane) uses a large amount of high-purity silicon organic matter, which is high in cost and has a long production cycle.
[0005] In addition, the above three methods have a common problem, that is, the products are all amorphous quartz sand particles. Compared with crystalline quartz, which has a clear melting temperature point, amorphous quartz sand only has a wide melting / softening temperature range. In the melting process of amorphous quartz sand into quartz glass products, a very wide melting / softening zone will be produced. The gas in this range (including the gas between the quartz sand particles and the gas generated inside the quartz sand particles during the melting process) is easily wrapped in the melting / softening zone during the melting process, and then bubbles, flocs and other defects are formed in the prepared quartz glass, reducing the mechanical properties, thermal stability and optical properties of the quartz product. Correspondingly, since crystalline quartz sand has a clear melting temperature point, the melting / softening zone produced during the smelting process is very narrow, and the gas is easier to escape during the smelting process. The result is that the quartz glass prepared with crystalline quartz sand has a lower content of defects such as bubbles and flocs, and the product quality is higher. Therefore, the preparation of crystalline synthetic quartz sand is the development direction of the high-purity quartz sand industry.
[0006] At present, the main method for synthesizing crystalline quartz sand is to produce crystalline α quartz (low-temperature quartz) quartz sand by a hydrothermal growth method similar to the preparation of artificial crystals. For example, Chinese patent application CN118183758A discloses a method for synthesizing high-purity silicon dioxide crystals by sequential online replenishment. This method requires the use of a high-pressure reactor for long-term growth under high temperature and high pressure conditions. Not only is the production cycle long and the output low, but the use of a hydrothermal reactor during the production process may also cause an explosion, which is quite dangerous. Therefore, it is costly, has poor product consistency, and is difficult to popularize and apply on a large scale. Summary of the invention
[0007] The purpose of the present invention is to solve the shortcomings of the prior art and propose a low-cost method for preparing high-purity crystalline cristobalite quartz sand. The high-purity crystalline cristobalite quartz sand is prepared by artificial synthesis, and has the advantages of high yield, low cost, high safety and industrialization.
[0008] To achieve the above object, the present invention adopts the following technical solutions: A method for preparing low-cost high-purity crystalline cristobalite quartz sand, the method comprising: Step S1: mixing a silicon source, high purity alkali and deionized water in a mass ratio of 1: (1-5): (10-50), and heating to 60° C. to 100° C. to prepare high purity water glass; Step S2: High-purity water glass and high-purity acid are mixed in a mass ratio of (1:0.1) to (1:10), stirred to form a precipitate, and the precipitate is sealed and allowed to stand for 1 to 5 days to ensure complete precipitation, and the growth process of the gel is used to separate and remove impurities, and finally the precipitate and the mixed acid are heated to 40° C. to 80° C. for aging treatment, and the aging treatment time is 1 to 5 days; Step S3: filtering and washing the precipitate with deionized water to clean the ions on the surface of the precipitate until the pH value of the filtrate reaches neutral; drying and dehydrating the precipitate at a temperature of 120° C. to 200° C. to obtain dry amorphous high-purity silica gel powder; Step S4: performing crystallization transformation and chlorination impurity removal on the amorphous high-purity silica gel powder: placing the amorphous high-purity silica gel powder in a high-temperature furnace, heating it to 1100°C to 1300°C at a heating rate of 2°C / min to 10°C / min and keeping it warm for 1 hour to 30 hours, and transforming it into crystalline cristobalite; in the later stage of the insulation, introducing chlorination gas into the high-temperature furnace for chlorination impurity removal, and the impurity removal process lasts for 0.5 hour to 10 hours; Step S5: using deionized water and dilute acid to wash the crystallized and impurity-free cristobalite to remove chlorides on the surface of the cristobalite, and drying to obtain high-purity crystalline cristobalite quartz sand.
[0009] Preferably, in step S1, the silicon source is a high-purity silicon material or a high-purity silicon ore, and the purity of the silicon source is higher than 4N. The high-purity silicon material can be waste, edge material or cutting waste of solar-grade silicon granules or solar-grade / semiconductor-grade silicon crystal pulling materials; or the silicon source is a silicon ore with a purity higher than 4N.
[0010] Preferably, in step S1, the high purity alkali is electronic grade high purity sodium hydroxide or potassium hydroxide, and the purity of the high purity alkali is not less than 99.99%.
[0011] Preferably, in step S1, the resistivity of the deionized water is greater than 16.5 MΩ·cm, and the total organic carbon is less than 20 ppmw.
[0012] Preferably, the heating method in step S1 is water bath heating or resistance heating.
[0013] Preferably, in step S2, the concentration of high-purity water glass is 5% to 35%.
[0014] Preferably, in step S2, the high-purity acid is one or more of an inorganic acid and an organic acid, and the concentration of the high-purity acid is 0.5 mol / L to 5.0 mol / L.
[0015] Preferably, the chlorinated gas introduced in step S4 is hydrogen chloride gas, chlorine gas or a mixture of the two.
[0016] Preferably, the purity of the high-purity crystalline cristobalite quartz sand obtained in step S5 is 5N to 7N.
[0017] Preferably, the high-purity crystalline cristobalite quartz sand obtained in step S5 has a particle size of 70 μm to 300 μm and a total impurity content of 0.5 ppmw to 10 ppmw.
[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: the preparation method of the present invention can synthesize high-purity crystalline cristobalite quartz sand at low cost, and the purity thereof can reach 5N to 7N, which is higher than the purity of 4N to 5N of naturally purified quartz sand. Meanwhile, compared with synthetic quartz sand produced by other methods, the preparation cost of the present invention is low, the output is high, and large-scale continuous production can be realized. Meanwhile, the synthesized quartz sand is in a crystalline state, and the quartz glass products produced by using the crystalline quartz sand have lower bubble and flocculent content and better mechanical, heat-resistant and optical properties than the amorphous synthetic quartz sand glass products.
[0019] The advantages of the present invention also lie in: 1. After the precipitation process, a long static aging process is adopted, and the dissolution and regrowth process of the precipitate in the liquid is utilized. At the solid-liquid interface, the segregation effect is utilized to make most of the impurities segregate into the liquid, so that the precipitate particles grow from small to large, and the precipitate particle size can reach the required level without consuming additional energy and extra time; 2. The process of crystallization transformation + chlorination impurity removal is adopted, and the alkali metal elements remaining in the amorphous high-purity silica gel powder are utilized to reduce the temperature and energy barrier of the crystallization transformation of quartz at high temperature. The amorphous high-purity silica gel powder can be completely transformed into crystalline cristobalite in a relatively short time. At the same time, chlorination gas is introduced in the later stage of heating to efficiently remove the alkali metal elements in the quartz lattice, and finally high-purity crystalline cristobalite quartz sand is synthesized, which greatly reduces the impurity content. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The present invention is a flowchart of a method for preparing high-purity crystalline cristobalite quartz sand according to some embodiments of the present invention.
[0021] Figure 2 The X-ray diffraction diagram of high-purity crystalline cristobalite quartz sand prepared in some embodiments of the present invention.
[0022] Figure 3 The figure is a particle size distribution diagram of high-purity crystalline cristobalite quartz sand prepared in some embodiments of the present invention. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below in conjunction with the accompanying drawings of the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention. It can be understood that some technical means of the various embodiments described herein can be replaced or combined with each other without conflict.
[0024] In the description of the present invention, if there are terms such as "first", "second", etc., they are only used to distinguish the objects described, and do not have any order or technical meaning. Therefore, the objects defined as "first", "second", etc. may explicitly or implicitly include one or more of the objects. In addition, "one" or "a" and similar words do not indicate a quantity limitation, but indicate the existence of at least one, and "multiple" means not less than two.
[0025] In the description of the present specification, reference to "one embodiment" or "some embodiments" etc. means that one or more embodiments of the present invention include a specific feature, structure or characteristic described in conjunction with the embodiment. Therefore, the phrases "in one embodiment", "in some embodiments", "in some other embodiments", "in some other embodiments", etc. appearing in different places in this specification do not necessarily refer to the same embodiment, but mean "one or more but not all embodiments", unless otherwise specifically emphasized in other ways.
[0026] The invention provides a low-cost preparation method of high-purity crystalline cristobalite quartz sand, which adopts an artificial synthesis method to prepare the high-purity crystalline cristobalite quartz sand, and has the advantages of high yield, low cost, high safety and industrialization.
[0027] Please refer to Figure 1 In some embodiments, the method for preparing the low-cost high-purity crystalline cristobalite quartz sand comprises: Step S1: Mix a silicon source, high purity alkali and deionized water in a mass ratio of 1: (1-5): (10-50), and heat to 60° C. to 100° C. to obtain high purity water glass.
[0028] Among them, the silicon source can be high-purity silicon material or high-purity silicon ore, and the purity of the silicon source is higher than 4N. For example, the silicon source can be waste, edge materials or cutting waste of solar-grade silicon granules or solar-grade / semiconductor-grade silicon crystal pulling materials; or, the silicon source uses silicon ore with a purity higher than 4N. It should be noted that the N in the purity grade here is the abbreviation of the English word "nine", which means the number of "9" in the purity grade. For example, 3N means a purity of 99.9%, 4N means a purity of 99.99%, and so on. In different application scenarios, the requirements for the purity of finished quartz sand may be different. It has been verified that the purity of quartz sand prepared with silicon ore as the silicon source may be slightly lower than that of quartz sand prepared with high-purity silicon as the silicon source. However, the cost of silicon ore is lower than that of solar-grade silicon. Therefore, in some scenarios where the purity requirements for quartz sand are not particularly high, natural silicon ore can be used as the silicon source, which can not only reduce the manufacturing cost, but also make the produced quartz sand reach a relatively high purity to meet the application requirements. In some scenarios where the purity requirements for quartz sand are higher, solar-grade silicon can be used as the silicon source to obtain higher-purity crystalline cristobalite quartz sand to meet the application requirements.
[0029] High purity alkali can be made of electronic grade high purity sodium hydroxide or potassium hydroxide, and the purity of high purity alkali is not less than 99.99%. The resistivity of deionized water is greater than 16.5MΩ·cm (megaohm·cm), and the total organic carbon (TOC, Total Organic Carbon) is less than 20ppmw. The heating method can be water bath heating or resistance heating.
[0030] Step S2: High-purity water glass and high-purity acid are mixed in a mass ratio of (1:0.1) to (1:10), stirred to form a precipitate, and the precipitate is sealed and allowed to stand for 1 to 5 days to ensure complete precipitation, and the growth process of the gel is used to separate and remove impurities, and finally the precipitate and the mixed acid are heated to 40° C. to 80° C. for aging treatment, and the aging treatment time is 1 to 5 days.
[0031] The concentration of high-purity water glass is 5% to 35%. The high-purity acid can be one or more of inorganic acid and organic acid. The high-purity inorganic acid can include hydrochloric acid (HCl), nitric acid (HNO3) or sulfuric acid (H2SO4), etc. The high-purity organic acid can include acetic acid (CH3COOH), oxalic acid (H2C2O4), citric acid (C6H8O7), etc. The concentration of high-purity acid is 0.5 mol / L (mole / liter) to 5.0 mol / L.
[0032] In step S2 of the present invention, the particle size of the precursor silicate precipitate is increased and the impurity content thereof is reduced by precipitation + segregation. After the precipitation process, a long static aging process is adopted, and the self-dissolution and regrowth process of the precipitate in the liquid are utilized, and the segregation effect is utilized at the solid-liquid interface to make most of the impurities segregate into the liquid, so that the precipitate particles are changed from small to large. Other methods for synthesizing quartz sand in the prior art use ion exchange columns to replace metal ions in the solution, which is costly, and the regeneration of the ion exchange columns also requires a lot of time and deionized water. In addition, other synthesis methods require additional granulation processes, including freezing, calcination, etc., which require consumption of additional energy. The preparation method of the present invention only requires sealed static and aging at a temperature of 40°C to 80°C, and the particle size of the precipitate can reach the requirements of quartz sand (70μm (micrometer) to 300μm) without consuming additional energy and extra time.
[0033] Step S3: Filter and rinse the precipitate with deionized water to clean the ions on the surface of the precipitate until the pH value of the filtrate reaches neutral, that is, the pH value of the filtrate reaches 7. Dry and dehydrate the precipitate at a temperature of 120° C. to 200° C. to obtain dry amorphous high-purity silica gel powder, which can be used as a quartz precursor.
[0034] Step S4: performing crystallization transformation and chlorination impurity removal on the amorphous high-purity silica gel powder: placing the amorphous high-purity silica gel powder in a high-temperature furnace, heating it to 1100°C to 1300°C at a heating rate of 2°C / min (degrees Celsius / minute) to 10°C / min and keeping it warm for 1 hour to 30 hours, so as to transform it into crystalline cristobalite; in the later stage of the insulation, introducing chlorination gas into the high-temperature furnace for chlorination impurity removal, the impurity removal process is 0.5 hour to 10 hours, and the impurity removal time does not exceed half of the insulation time.
[0035] The chlorination gas may be hydrogen chloride (HCl) gas, chlorine (Cl2) gas or a mixture of the two. The high temperature furnace may be a high temperature furnace device in the prior art, such as a high temperature tube furnace. The flow rate of the chlorination gas may be reasonably set according to the furnace tube size of the high temperature furnace and the quality of the amorphous high purity silica gel powder. For example, in some embodiments, the high temperature furnace adopts a commonly used tube furnace, and the flow rate of the chlorination gas is 5L / h (liters / hour) to 8L / h.
[0036] In step S4 of the present invention, a process of crystallization transformation + chlorination impurity removal is adopted, and the alkali metal elements (with a content range of 1 to 2000 ppmw) that are inevitably residual in the amorphous high-purity silica gel powder are utilized to reduce the temperature and energy barrier of the crystallization transformation of quartz at high temperature, so that the amorphous high-purity silica gel powder can be completely transformed into crystalline cristobalite in a relatively short time. At the same time, chlorination gas is introduced in the later stage of heating to efficiently remove the alkali metal elements in the quartz lattice, and finally high-purity crystalline cristobalite quartz sand is synthesized, greatly reducing the impurity content.
[0037] Step S5: using deionized water and dilute acid to wash the crystallized and impurity-free cristobalite to remove chlorides on the surface of the cristobalite, and drying to obtain high-purity crystalline cristobalite quartz sand.
[0038] Among them, the resistivity of deionized water is greater than 16.5MΩ·cm, and the total organic carbon (TOC) is less than 20ppmw. The dilute acid can be an organic acid or an inorganic acid. The inorganic acid can include hydrochloric acid (HCl), nitric acid (HNO3) or sulfuric acid (H2SO4), etc., and the organic acid can include acetic acid (CH3COOH), oxalic acid (H2C2O4), citric acid (C6H8O7), etc. The concentration of the dilute acid can be reasonably set according to the type of acid actually selected. Preferably, the dilute acid used in step S5 can be the same acid with different concentrations as the high-purity acid in step S2 for easy management.
[0039] In the preparation method of the present invention, firstly, high-purity water glass is prepared by using silicon source, high-purity alkali and deionized water, and then the particle size of the precursor silicate precipitate is increased and the impurity content thereof is reduced by precipitation + segregation; then, amorphous high-purity silica gel powder is prepared by washing with deionized water and slowly drying; then, a proper amount of alkali metal impurities (the content of which is in the range of 1 to 2000 ppmw) present in the amorphous high-purity silica gel powder is used to reduce its crystallization temperature, and in the subsequent crystallization transformation + chlorination impurity removal process, the amorphous high-purity silica gel powder is first heated to be transformed into crystalline cristobalite, and then chlorination gases such as hydrogen chloride (HCl) gas and chlorine (Cl2) are introduced for chlorination impurity removal to remove alkali metal impurities, and finally synthetic high-purity crystalline cristobalite quartz sand is obtained.
[0040] In one embodiment, the high-purity crystalline cristobalite sand synthesized by the above-mentioned preparation method is tested by an X-ray diffractometer to obtain the following Figure 2 From the X-ray diffraction diagram (XRD diagram) shown, it can be seen that the diagram has a sharper diffraction peak, indicating that there is a crystalline structure with better crystallinity in the quartz sand.
[0041] In some embodiments, the high-purity crystalline cristobalite quartz sand synthesized by the above preparation method is detected by a laser particle size analyzer, and the following is obtained: Figure 3From the particle size distribution diagram shown, it can be seen that more than 95% of the overall particle size distribution of the synthetic high-purity crystalline cristobalite quartz sand is between 70μm and 300μm.
[0042] Generally speaking, the purity of natural purified quartz sand is 4N to 5N, while the purity of the high-purity crystalline cristobalite quartz sand synthesized by the above preparation method can reach 5N to 7N, and the total impurity content is 0.5ppmw to 10ppmw. Therefore, compared with the naturally purified quartz sand, the high-purity crystalline cristobalite quartz sand synthesized by the preparation method of the present invention has higher purity and lower impurity content.
[0043] At the same time, the quartz sand synthesis method in the prior art needs to consume additional energy and time, while the preparation method of the present invention adopts precipitation + segregation, crystallization transformation + chlorination impurity removal and other processes, which can reduce the manufacturing cost, increase the output, and realize large-scale continuous production. At the same time, the synthesized quartz sand is in a crystalline state, and the quartz glass products produced using the crystalline quartz sand have lower bubble and floc content and better mechanical, heat-resistant and optical properties.
[0044] In other preferred embodiments, the method for preparing high-purity crystalline cristobalite quartz sand comprises: Step S1: Using high-purity silicon as a silicon source, high-purity silicon, high-purity alkali (electronic grade high-purity sodium hydroxide or potassium hydroxide) and deionized water (resistivity greater than 16.5 MΩ·cm, TOC less than 20 ppmw) are mixed in a mass ratio of 1: (2-4): (20-40), and heated to 60° C. to 85° C. to obtain high-purity water glass.
[0045] Step S2: High-purity water glass and high-purity acid are mixed in a mass ratio of (1:0.5) to (1:8.5), stirred to form a precipitate, and the precipitate is sealed and allowed to stand for 2 to 4 days to ensure complete precipitation, and the growth process of the gel is used for segregation and impurity removal, and finally the precipitate and the mixed acid are heated to 45° C. to 75° C. for aging treatment, and the aging treatment time is 2 to 4 days.
[0046] Step S3: Filter and rinse the precipitate with deionized water to clean the ions on the surface of the precipitate until the pH value of the filtrate reaches neutral, that is, the pH value of the filtrate reaches 7. Dry and dehydrate the precipitate at a temperature of 140° C. to 190° C. to obtain dry amorphous high-purity silica gel powder.
[0047] Step S4: crystallization transformation and chlorination removal of impurities on the amorphous high-purity silica gel powder: the amorphous high-purity silica gel powder is placed in a high-temperature furnace, heated to 1100°C to 1300°C at a heating rate of 3°C / min to 8°C / min and kept warm for 5 hours to 25 hours to transform it into crystalline cristobalite; in the later stage of the insulation, chlorination gas is introduced into the high-temperature furnace for chlorination removal, and the impurity removal process takes 1 hour to 5 hours.
[0048] Step S5: using deionized water and dilute acid to wash the crystallized and impurity-free cristobalite to remove chlorides on the surface of the cristobalite, and drying to obtain high-purity crystalline cristobalite quartz sand.
[0049] The high-purity crystalline quartz sand synthesized by the preparation method has higher purity and lower impurity content. At the same time, it can reduce manufacturing costs, increase output, and achieve large-scale continuous production. The synthesized quartz sand is in a crystalline state, and the quartz glass products produced by using the crystalline quartz sand have lower bubble and floc content and better mechanical, heat-resistant and optical properties. Example 1
[0050] The preparation method of high-purity crystalline cristobalite quartz sand comprises: Step S1: solar-grade silicon, electronic-grade high-purity sodium hydroxide and deionized water (resistivity greater than 16.5 MΩ·cm, TOC less than 20 ppmw) are mixed in a mass ratio of 1:3:30, and heated to 60° C. to obtain high-purity sodium water glass.
[0051] Step S2: slowly add 2 mol / L electronic grade high purity nitric acid into 13% high purity sodium water glass, the mass ratio of high purity sodium water glass to high purity nitric acid solution is 1:2, and stir the solution until the precipitate is completely formed, and let the precipitate and the solution stand together for 24 hours for segregation and impurity removal, and then put the precipitate and the mixed acid on a 50°C heating plate for aging treatment for 24 hours.
[0052] Step S3: Filter and rinse the precipitate with deionized water to clean the ions on the surface of the precipitate until the pH value of the filtrate reaches neutral, that is, the pH value of the filtrate reaches 7. Dry and dehydrate the filter cake on a heating plate at 150° C. to obtain dry amorphous high-purity silica gel powder.
[0053] Step S4: performing crystallization transformation and chlorination removal of impurities on the amorphous high-purity silica gel powder: placing the amorphous high-purity silica gel powder in a high-temperature tube furnace, heating it to 1100° C. at a heating rate of 3° C. / min and keeping it warm for 3 hours to transform it into crystalline cristobalite; in the last 1.5 hours of the insulation, introducing dry HCl gas into the high-temperature tube furnace for chlorination removal of impurities, and the flow rate of HCl gas is 6 L / h.
[0054] Step S5: using deionized water and dilute nitric acid to wash the crystallized and impurity-free cristobalite to remove chlorides on the surface of the cristobalite, and drying to obtain high-purity crystalline cristobalite quartz sand.
[0055] Afterwards, the obtained high-purity crystalline cristobalite quartz sand was subjected to inductively coupled plasma (ICP) testing, and the test results are shown in Table 1 (where “~” indicates that the content of the element is below the detection limit): Table 1 ICP test results of quartz sand in Example 1 Impurity Elements Li Na K Al Fe Ti Ca Content (ppmw) ~ 1.1 ~ 0.2 0.4 0.1 0.2 Impurity Elements Mg Cr Ni Mn Cu B total Content (ppmw) ~ ~ ~ ~ ~ ~ 2.0 It can be seen that the total impurity content in the high-purity crystalline cristobalite quartz sand is 2.0 ppmw, and the purity reaches 5N8 grade. Therefore, the crystalline cristobalite quartz sand synthesized by the above preparation method has higher purity and lower impurity content, and the quartz glass products produced by using the high-purity crystalline cristobalite quartz sand have lower bubble and floc content and better mechanical, heat-resistant and optical properties. Example 2
[0056] The preparation method of high-purity crystalline cristobalite quartz sand comprises: Step S1: solar-grade silicon, electronic-grade potassium hydroxide and deionized water (resistivity greater than 16.5 MΩ·cm, TOC less than 20 ppmw) are mixed in a mass ratio of 1:4:50, and heated to 70° C. to obtain high-purity potassium water glass.
[0057] Step S2: slowly adding electronic grade high-purity hydrochloric acid with a concentration of 4.5 mol / L into high-purity potassium water glass with a concentration of 10%, wherein the mass ratio of high-purity potassium water glass to high-purity hydrochloric acid solution is 1:0.75, and stirring the solution until the precipitate is completely generated, and placing the precipitate and the solution together for 3 days, and utilizing the growth process of the gel to perform segregation and impurity removal; finally, placing the precipitate and the mixed acid together on a heating plate at 60° C. for aging treatment for 2 days.
[0058] Step S3: Filter and rinse the precipitate with deionized water to clean the ions on the surface of the precipitate until the pH value of the filtrate reaches neutral, that is, the pH value of the filtrate reaches 7. Dry and dehydrate the filter cake on a heating plate at 170° C. to obtain dry amorphous high-purity silica gel powder.
[0059] Step S4: crystallization transformation and chlorination removal of impurities on the amorphous high-purity silica gel powder: place the amorphous high-purity silica gel powder in a high-temperature tube furnace, heat it to 1250°C at a heating rate of 5°C / min and keep it warm for 10 hours to transform it into crystalline cristobalite; in the last 3 hours of insulation, introduce dry HCl and Cl2 mixed gas into the high-temperature tube furnace, and the flow rate of chlorination gas is 8L / h.
[0060] Step S5: using deionized water and dilute hydrochloric acid to wash the crystallized and impurity-free cristobalite to remove chlorides on the surface of the cristobalite, and drying to obtain high-purity crystalline cristobalite quartz sand.
[0061] Afterwards, the obtained high-purity crystalline cristobalite quartz sand was subjected to inductively coupled plasma (ICP) testing, and the test results are shown in Table 2 (where “~” indicates that the content of the element is below the detection limit): Table 2 ICP test results of quartz sand in Example 2 Impurity Elements Li Na K Al Fe Ti Ca Content (ppmw) ~ ~ ~ 0.1 0.1 ~ 0.2 Impurity Elements Mg Cr Ni Mn Cu B total Content (ppmw) ~ ~ ~ ~ ~ 0.1 0.5 It can be seen that the total impurity content in the high-purity crystalline cristobalite quartz sand is 0.5 ppmw, and the purity reaches 6N5 grade. Therefore, the crystalline cristobalite quartz sand synthesized by the above preparation method has higher purity and lower impurity content, and the quartz glass products produced by using the high-purity crystalline cristobalite quartz sand have lower bubble and floc content and better mechanical, heat-resistant and optical properties. Example 3
[0062] The preparation method of high-purity crystalline cristobalite quartz sand comprises: Step S1: solar-grade silicon, electronic-grade potassium hydroxide and deionized water (resistivity greater than 16.5 MΩ·cm, TOC less than 20 ppmw) are mixed in a mass ratio of 1:2.5:20, and heated to 65° C. to obtain high-purity potassium water glass.
[0063] Step S2: slowly add 0.5 mol / L electronic grade high purity sulfuric acid into 25% high purity potassium water glass, the mass ratio of high purity potassium water glass to high purity sulfuric acid solution is 1:5, and stir the solution until the precipitate is completely generated, and let the precipitate and the solution stand together for 3 days, and use the growth process of gel to segregate and remove impurities; finally, put the precipitate and the mixed acid together on a heating plate at 75° C. for aging treatment for 3 days.
[0064] Step S3: Filter and rinse the precipitate with deionized water to clean the ions on the surface of the precipitate until the pH value of the filtrate reaches neutral, that is, the pH value of the filtrate reaches 7. Dry and dehydrate the filter cake on a heating plate at 200° C. to obtain dry amorphous high-purity silica gel powder.
[0065] Step S4: crystallization transformation and chlorination removal of impurities on the amorphous high-purity silica gel powder: place the amorphous high-purity silica gel powder in a high-temperature tube furnace, heat it to 1100°C at a heating rate of 5°C / min and keep it warm for 5 hours to transform it into crystalline cristobalite; in the last 2 hours of insulation, introduce dry HCl and Cl2 mixed gas into the high-temperature tube furnace for chlorination removal of impurities, and the flow rate of the chlorination gas is 8L / h.
[0066] Step S5: using deionized water and dilute acid to wash the crystallized and impurity-free cristobalite to remove chlorides on the surface of the cristobalite, and drying to obtain high-purity crystalline cristobalite quartz sand.
[0067] Afterwards, the obtained high-purity crystalline cristobalite quartz sand was subjected to inductively coupled plasma (ICP) testing, and the test results are shown in Table 3 (wherein, “~” indicates that the content of the element is below the detection limit): Table 3 ICP test results of quartz sand in Example 3 Impurity Elements Li Na K Al Fe Ti Ca Content (ppmw) ~ 0.1 3.8 ~ 0.1 0.1 0.2 Impurity Elements Mg Cr Ni Mn Cu B total Content (ppmw) 0.1 ~ ~ ~ ~ 0.1 4.5 It can be seen that the total impurity content in the high-purity crystalline cristobalite quartz sand is 4.5 ppmw, and the purity reaches 5N5 grade. Therefore, the crystalline cristobalite quartz sand synthesized by the above preparation method has higher purity and lower impurity content, and the quartz glass products produced by using the high-purity crystalline cristobalite quartz sand have lower bubble and floc content and better mechanical, heat-resistant and optical properties. Example 4
[0068] The preparation method of high-purity crystalline cristobalite quartz sand comprises: Step S1: The washed natural silicon ore, electronic grade potassium hydroxide and deionized water (resistivity greater than 16.5 MΩ·cm, TOC less than 20 ppmw) are mixed in a mass ratio of 1:3:10, and heated to 65° C. to obtain high-purity potassium water glass.
[0069] Step S2: slowly add 3 mol / L electronic grade high purity nitric acid into 18% high purity potassium water glass, the mass ratio of high purity potassium water glass to high purity sulfuric acid solution is 1:1.5, and stir the solution until the precipitate is completely generated, and let the precipitate and the solution stand together for 2 days, and use the growth process of gel to segregate and remove impurities; finally, put the precipitate and the mixed acid together on a heating plate at 75°C for aging treatment for 2 days.
[0070] Step S3: Filter and rinse the precipitate with deionized water to clean the ions on the surface of the precipitate until the pH value of the filtrate reaches neutral, that is, the pH value of the filtrate reaches 7. Dry and dehydrate the filter cake on a heating plate at 190° C. to obtain dry amorphous high-purity silica gel powder.
[0071] Step S4: crystallization transformation and chlorination removal of the amorphous high-purity silica gel powder: place the amorphous high-purity silica gel powder in a high-temperature tube furnace, heat it to 1100°C at a heating rate of 3°C / min and keep it warm for 2 hours to transform it into crystalline cristobalite; in the last hour of insulation, introduce dry HCl and Cl2 mixed gas into the high-temperature tube furnace for chlorination removal, and the flow rate of the chlorination gas is 6L / h.
[0072] Step S5: using deionized water and dilute acid to wash the crystallized and impurity-free cristobalite to remove chlorides on the surface of the cristobalite, and drying to obtain high-purity crystalline cristobalite quartz sand.
[0073] Afterwards, the obtained high-purity crystalline cristobalite quartz sand was subjected to inductively coupled plasma (ICP) testing, and the test results are shown in Table 4 (wherein, “~” indicates that the content of the element is below the detection limit): Table 4 ICP test results of quartz sand in Example 4 Impurity Elements Li Na K Al Fe Ti Ca Content (ppmw) ~ 0.1 5.6 2.8 0.6 0.2 0.4 Impurity Elements Mg Cr Ni Mn Cu B total Content (ppmw) 0.1 ~ ~ ~ ~ ~ 9.8 It can be seen that the total impurity content in the high-purity crystalline cristobalite quartz sand is 9.8ppmw, and the purity reaches 5N grade. Therefore, the crystalline cristobalite quartz sand synthesized by the above preparation method has higher purity and lower impurity content, and the quartz glass products produced by the high-purity crystalline cristobalite quartz sand have lower bubble and floc content and better mechanical, heat-resistant and optical properties. It should be noted that in step 1 of this embodiment, the silicon source uses natural silicon ore. Although the purity of the obtained quartz sand is slightly lower than that of the quartz sand obtained by using solar-grade silicon as the silicon source, the cost of natural silicon ore is lower than that of solar-grade silicon. Therefore, in some scenarios where the purity requirements for quartz sand are not particularly high, natural silicon ore can be used as the silicon source, which can not only reduce the manufacturing cost, but also make the obtained quartz sand reach a relatively high purity to meet the application requirements.
[0074] In summary, the present invention provides a low-cost preparation method of high-purity crystalline cristobalite quartz sand, which comprises the following steps: firstly, high-purity silicon or high-purity silicon ore, high-purity alkali and deionized water are used to prepare high-purity water glass, and then the particle size of the precursor silicic acid precipitate is increased and the impurity content thereof is reduced by precipitation + segregation; then, amorphous high-purity silica gel powder is prepared by deionized water washing and slow drying; then, an appropriate amount of alkali metal impurities present in the amorphous high-purity silica gel powder is used to reduce its crystallization temperature, and in the subsequent crystallization transformation + chlorination impurity removal process, the amorphous high-purity silica gel powder is first heated and transformed into crystalline cristobalite, and then chlorination gas is introduced for chlorination impurity removal to remove the alkali metal impurities, and finally, synthetic high-purity crystalline cristobalite quartz sand is obtained.
[0075] The high-purity crystalline cristobalite quartz sand synthesized by the preparation method of the present invention has higher purity and lower impurity content. At the same time, the preparation method of the present invention adopts processes such as precipitation+segregation, crystallization transformation+chlorination impurity removal, which can reduce manufacturing costs, increase output, and realize large-scale continuous production. The synthesized quartz sand is in a crystalline state, and the quartz glass products produced by using the crystalline quartz sand have lower bubble and floc content and better mechanical, heat-resistant and optical properties.
[0076] The present invention has been described by the above-mentioned relevant embodiments, however, the above-mentioned embodiments are only examples for implementing the present invention. It must be pointed out that the disclosed embodiments do not limit the scope of the present invention. On the contrary, changes and modifications made without departing from the spirit and scope of the present invention are all within the scope of patent protection of the present invention.
Claims
1. A method for preparing high-purity crystalline cristobalite quartz sand, characterized in that: The preparation method of the high-purity crystalline cristobalite quartz sand comprises: Step S1: mixing a silicon source, high purity alkali and deionized water in a mass ratio of 1: (1-5): (10-50), and heating to 60° C. to 100° C. to prepare high purity water glass; Step S2: High-purity water glass and high-purity acid are mixed in a mass ratio of (1:0.1) to (1:10), stirred to form a precipitate, the precipitate is sealed and allowed to stand for 1 to 5 days to ensure complete precipitation, and the growth process of the gel is used to separate and remove impurities, and finally the precipitate and the mixed acid are heated to 40° C. to 80° C. for aging treatment, and the aging treatment time is 1 to 5 days; Step S3: filtering and washing the precipitate with deionized water to clean the ions on the surface of the precipitate until the pH value of the filtrate reaches neutral; drying and dehydrating the precipitate at a temperature of 120° C. to 200° C. to obtain dry amorphous high-purity silica gel powder; Step S4: performing crystallization transformation and chlorination impurity removal on the amorphous high-purity silica gel powder: placing the amorphous high-purity silica gel powder in a high-temperature furnace, heating it to 1100°C to 1300°C at a heating rate of 2°C / min to 10°C / min and keeping it warm for 1 hour to 30 hours, and transforming it into crystalline cristobalite; in the later stage of the insulation, introducing chlorination gas into the high-temperature furnace for chlorination impurity removal, and the impurity removal process lasts for 0.5 hour to 10 hours; Step S5: using deionized water and dilute acid to wash the crystallized and impurity-free cristobalite to remove chlorides on the surface of the cristobalite, and drying to obtain high-purity crystalline cristobalite quartz sand.
2. The method for preparing high-purity crystalline cristobalite quartz sand according to claim 1, characterized in that: In step S1, the silicon source is a high-purity silicon material or a high-purity silicon ore, and the purity of the silicon source is higher than 4N.
3. The method for preparing high-purity crystalline cristobalite quartz sand according to claim 1, characterized in that: In step S1, the high purity alkali is electronic grade high purity sodium hydroxide or potassium hydroxide, and the purity of the high purity alkali is not less than 99.99%.
4. The method for preparing high-purity crystalline cristobalite quartz sand according to claim 1, characterized in that: In step S1, the resistivity of the deionized water is greater than 16.5 MΩ·cm, and the total organic carbon is less than 20 ppmw.
5. The method for preparing high-purity crystalline cristobalite quartz sand according to claim 1, characterized in that: The heating method in step S1 is water bath heating or resistance heating.
6. The method for preparing high-purity crystalline cristobalite quartz sand according to claim 1, characterized in that: In step S2, the concentration of high-purity water glass is 5% to 35%.
7. The method for preparing high-purity crystalline cristobalite quartz sand according to claim 1, characterized in that: In step S2, the high-purity acid is one or more of an inorganic acid and an organic acid, and the concentration of the high-purity acid is 0.5 mol / L to 5.0 mol / L.
8. The method for preparing high-purity crystalline cristobalite quartz sand according to claim 1, characterized in that: The chlorinated gas introduced in step S4 is hydrogen chloride gas, chlorine gas or a mixture of the two.
9. The method for preparing high-purity crystalline cristobalite quartz sand according to claim 1, characterized in that: The purity of the high-purity crystalline cristobalite quartz sand obtained in step S5 is 5N to 7N.
10. The method for preparing high-purity crystalline cristobalite quartz sand according to claim 1, characterized in that: The high-purity crystalline cristobalite quartz sand obtained in step S5 has a particle size of 70 μm to 300 μm and a total impurity content of 0.5 ppmw to 10 ppmw.
Citation Information
Patent Citations
Method for synthesizing silicon dioxide powder by using organosilane
CN114105150A
Method for preparing high-purity quartz sand from superfine silicon powder
CN115676842A
Preparation method of titanium-doped synthetic quartz sand
CN116375315A
Method for synthesizing high-purity silicon dioxide crystals through successive online supply
CN118183758A
Quartz crystal type conversion metal element gasification integration purification method
CN102674377A
Cited By
Method for converting 6N-grade quartz sand into high-purity alpha-cristobalite by doping and coating
CN122079181A